Influence of Discipline Related Factors on Career Choice of Medical Students, Intern Doctors and Recent Graduates in Bangladesh (Bangladesh Journal of Medical Education, 2024)
Background: The decisions made by graduates affect the workforce planning for the healthcare delivery system and higher education programs. This study sought to evaluate the elements impacting the career choices of MBBS final year medical students, intern doctors, and recent graduates in Bangladesh.Methods: This cross-sectional study was conducted from July 2022 to June 2023 after getting institutional ethical approval. It was conducted upon 640 respondents form conveniently selected six medical colleges of Bangladesh. After taking consent from the college authorities and respondents, data were collected by administering a self-administered semi-structured questionnaire from 300 students, 200 interns and 140 recent medical graduates. Data were analyzed by SPSS 24.0 and presented by tables and graphs. Convenience sampling technique was used for selection of the respondents and medical colleges.Results: This study showed that, (85.7%) MBBS final year students, (67%) intern doctors and all  recent medical graduates wanted post-graduation qualification for their future career. On the other hand, (14.3%) MBBS final year students and (33%) intern doctors did not want post-graduation for their future career. The popular choice among respondents was physical medicine and rehabilitation (7.2%) as 1st choice and Ophthalmology (6.8%) as 2nd choice. After summing up all choices the overall first three ranked choices were Pediatrics, Pathology and Orthopaedic surgery. The leading reasons for selecting a future career were due to family influence (67.8%), influenced by practicing doctor (54.8%) and other senior medical students (53.1%). Majority of respondents expressed that they developed interest during enrolling in the subject in the respective field (mean score = 3.41 out of 5). Other contributing factors that influence respondents on choosing their future career due to high demanding career path (mean score = 3.36 out of 5) and availability of the course subject (mean score = 3.12 out of 5).Conclusion: In this regard, the study stated that a variety of impacts and factors at various points in medical education may assist students and future doctors in selecting their career specialization in accordance with the requirements of the local healthcare delivery system.BJME, Volume-15, Issue-02, July 2024: 27-35